A new species of Barringtonia (Lecythidaceae) from Thailand and taxonomic notes on B. schmidtii - Thammarong, Woranart; Chantaranothai, Pranom; Pornpongrungrueng, Pimwadee (Phytotaxa, 2015)
A new species of Barringtonia (Lecythidaceae), B. thailandica, is described from eastern Thailand. This species resembles B. acutangula in habit, leaf and flower characters, but differs mainly by its ellipsoid-shaped fruit with eight ribs. Additionally, B. schmidtii is reinstated as an independent species and it can be distinguished from its closely related taxa B. acutangula by its swollen leaf base, tomentose rachis, hypanthium and sepals, yellow filaments as well as obovoid-shaped, 4-angled and puberulent fruit. B. bicolor and B. badia are conspecific with B. schmidtii.